2004
DOI: 10.1007/s00417-003-0847-x
|View full text |Cite
|
Sign up to set email alerts
|

Retinal vessel reaction in response to chromatic flickering light

Abstract: Retinal vessel diameter dilation is a reproducible response to the applied flicker stimuli. This finding supports the existence of neurovascular coupling in the human retina. Flicker stimulation in either red-green or blue-green might be a useful stimulus for examination of retinal vessel behavior to regulatory demands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 21 publications
3
39
0
1
Order By: Relevance
“…results confirm previous observations in humans 15 and animals 22 that most of the arterial dilation occurs within the first 10 seconds of stimulation. Additionally no significant increase in maximum dilation was found in arteries between flicker durations of 5, 7, 10, and 20 seconds.…”
Section: Effect Of Flicker Duration On Retinal Vessel Dilationsupporting
confidence: 82%
See 2 more Smart Citations
“…results confirm previous observations in humans 15 and animals 22 that most of the arterial dilation occurs within the first 10 seconds of stimulation. Additionally no significant increase in maximum dilation was found in arteries between flicker durations of 5, 7, 10, and 20 seconds.…”
Section: Effect Of Flicker Duration On Retinal Vessel Dilationsupporting
confidence: 82%
“…Although there has been prior research aimed at determining the best FL frequency, 13 effects of illumination, 15 and some comparison between two flicker durations 15 there has, as far as we know, been no systematic effort made to examine the effects of shorter FL durations and hence the time-course of retinal vessel dilation and constriction due to FL provocation as a function of FL duration.…”
Section: Effect Of Flicker Duration On Retinal Vessel Dilationmentioning
confidence: 99%
See 1 more Smart Citation
“…[44][45][46] Regarding the localized nature of SVP, while many reports assumed a constant venous flow upstream to the SVP site, pulsation has been observed using various techniques. 45,[47][48][49][50] Clearly, the constancy of the pulsation waveform along primary veins requires further study. We found that waveforms differ markedly between subjects; hence, a higher temporal resolution for better characterization should be sought in future investigations.…”
Section: Limitationsmentioning
confidence: 99%
“…[8][9][10] Most of the published data rely on the observation of vascular caliber variations to draw conclusions from vessel diameter changes on flow changes. [11][12][13][14] Typically, the diameter of a vessel is assessed by fundus photographic techniques, which allow for the real time evaluation of retinal vessel diameter. A large number of studies have been performed to assess vessel diameter changes during stimulation with diffuse luminance flicker in healthy subjects under normal conditions 9,11 or during oxygen breathing, 15 as well as in patients with diabetes, 16,17 glaucoma, 18,19 or systemic hypertension.…”
mentioning
confidence: 99%